2009
DOI: 10.1080/13623690902943339
|View full text |Cite
|
Sign up to set email alerts
|

Iraqi children's rights: building a system under fire

Abstract: War violates every human right of children. In recent years, the lives of Iraqi children and the livelihoods of their families have become precarious. Conflict has split the communities where they live and taken the lives of hundreds of their friends and family members. The literature focuses on the negative effects of armed conflict on Iraqi children, and the steps that need to be taken to ameliorate their condition by adapting evidence based but culturally sensitive measures. A comprehensive solution to chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In the area of legislation and human rights, an Iraqi Child Protection Act should ¢ll the gap and ensure that children are brought up in a protective and healthy environment focused on the best interests of the child (AlObaidi et al, 2009b).…”
Section: Camh Plans and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of legislation and human rights, an Iraqi Child Protection Act should ¢ll the gap and ensure that children are brought up in a protective and healthy environment focused on the best interests of the child (AlObaidi et al, 2009b).…”
Section: Camh Plans and Strategiesmentioning
confidence: 99%
“…Addressing these requires a holistic, rights based approach that can provide resources to meet their basic needs, advocate for their security and protection, as well as recognise and meet the needs of more vulnerable children, or refer them to other agencies with appropriate resources (Jones, 2008). Malnutrition, deterioration of education, a high and increased rate of truancy, child labour, tra⁄cking of children and involvement of children with militia and insurgency groups threatens the wellbeing of Iraqi children (AlObaidi, Je¡ery, Scarth & Albadawi, 2009b). In recent decades, wars, international sanctions, internal unrest, and massive civilian displacements within, and beyond, its borders have dominated the history of Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…These teachers described a high need for in‐house training and programmes for school‐based management of mental health and behavioural problems, indicating both the importance and the acceptability of such programmes for future development. It is essential to build the capacity of Iraqi educational professionals through continuing health and medical educational opportunities, covering topics such as learning techniques, early detection of health and mental health difficulties, and working with families to improve children's potential (Al‐Obaidi et al., ). Other studies have noted that disruptive behaviour prevents teachers from maintaining an orderly, safe and productive environment, and constitutes a major barrier to learning for a substantial proportion of students.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Iraq-Iran War (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988) and the 2003 US-led invasion, Iraqis have experienced severe deprivation caused by many years of war, economic embargos and civil unrest. High levels of armed violenceresulting in deaths, injuries, psychological trauma and bereavement in children and families (Hicks et al, 2011a;Hicks, Dardagan, Bagnall, Spagat, & Sloboda, 2011b)poverty, and failures of education and health systems have affected the wellbeing of Iraqis, especially of the children and adolescents (Al-Obaidi, Jeffrey, Scarth, & Albadawi, 2009) who form half of Iraq's population of approximately 32 million (Central Organization for Statistics, 2009). The contribution of warrelated and societal trauma to short-and long-term mental health problems in children and adolescents has been well documented (Betancourt & Khan, 2008;Masten & Narayan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have also indicated problems of drug and sexual abuse in children and adolescents in Iraq (AlObaidi et al, 2009b), but it is difficult to know the real scope of such problems. This author and his colleagues (2010b) reported that there were only 1.3% cases of drug abuse registered in a clinical sample of children and adolescents in Iraq.…”
Section: Child Mental Health In Iraq: Scope Of the Problem And Availamentioning
confidence: 99%